2019
DOI: 10.1002/jbmr.3686
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Decreases Hepatic 25-Hydroxylase Activity Causing Low Serum 25-Hydroxyvitamin D

Abstract: Normal vitamin D homeostasis is critical for optimal health; nevertheless, vitamin D deficiency is a worldwide public health problem. Vitamin D insufficiency is most commonly due to inadequate cutaneous synthesis of cholecalciferol and/or insufficient intake of vitamin D, but can also arise as a consequence of pathological states such as obesity. Serum concentrations of 25(OH)D (calcidiol) are low in obesity, and fail to increase appropriately after vitamin D supplementation. Although sequestration of vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
72
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 26 publications
(41 reference statements)
4
72
1
4
Order By: Relevance
“…The causality (in whatever direction) between obesity/diabetes and low vitamin D status is, however, not proven. In a recent JBMR article, Roizen and colleagues clearly demonstrated that the serum concentration of 25OHD is substantially lower (~−20%) in serum of obese mice (fed a high‐fat diet) compared with normal‐weight mice, whereas serum concentrations of vitamin D 3 itself were similar in both groups . This is not a surprise because serum 25OHD concentrations in overweight or obese humans are virtually systematically lower than in normal subjects in many different areas of the world having different sun exposure or dietary habits .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The causality (in whatever direction) between obesity/diabetes and low vitamin D status is, however, not proven. In a recent JBMR article, Roizen and colleagues clearly demonstrated that the serum concentration of 25OHD is substantially lower (~−20%) in serum of obese mice (fed a high‐fat diet) compared with normal‐weight mice, whereas serum concentrations of vitamin D 3 itself were similar in both groups . This is not a surprise because serum 25OHD concentrations in overweight or obese humans are virtually systematically lower than in normal subjects in many different areas of the world having different sun exposure or dietary habits .…”
mentioning
confidence: 99%
“…PGC1α also induced hepatic and renal expression of CYP24A1 several‐fold, again mediated by the GR‐PGC1α‐ERRα pathway (but much less than the 100‐fold induction by 1,25(OH) 2 D). Other major fat‐regulating nuclear receptors are less likely involved, as the ENCODE project did not find consensus sequences for nuclear receptor (VDR) binding sites in promoters of genes involved in fat metabolism in the liver, such as constitutive androstane receptor (CAR), pregnane X receptor (PXR), or peroxisome proliferator‐activated receptor (PPAR) binding sites in the proximal promoter of mouse or human CYP2R1 (http://www.cbrc.jp/htbin/nph-tfsearch), but several binding sites for NFkB were identified …”
mentioning
confidence: 99%
“…
We thank Landrier and colleagues for their thoughtful comments regarding our recent publication regarding the role of decreased expression of CYP2R1 as a basis for reduced circulating levels of 25(OH)D in obese mice. (1) First, Landrier and colleagues point out one of the weaknesses that we ourselves had noted in our article, specifically that the cholecalciferol content of the two diets was not identical. They further assert that when diet composition is adjusted for vitamin D intake, obese mice show no differences from lean mice in serum 25(OH)D 3 concentrations.
…”
mentioning
confidence: 86%
“…Indeed, when the concentration of cholecalciferol is balanced between control and HF diets, to bring the same amounts of cholecalciferol to mice, taking into account the lowest consumption of HF diet, (8) the decrease of total 25(OH)D is not obvious. (2,3,9) In this context, it is surprising that in their study, Roizen et al (1) did not adjust the quantity of cholecalciferol between groups by increasing the cholecalciferol concentration in the HF diet. At the opposite, the concentration of cholecalciferol was reduced in the HF group (2.1 UI/g) compared with the control group (3.3 UI/g).…”
mentioning
confidence: 90%
“…To the Editor, Roizen et al (1) published in the Journal of Bone and Mineral Research (JBMR) an interesting study related to the vitamin D metabolism in the context of obesity. Indeed, authors reported that a high fat (HF) diet resulted in modification of CYP2R1 expression (mRNA and protein), leading to a decrease of 25hydroxylase activity in the liver, which could explain the reduced serum 25-hydroxyvitamin D. Such observation is clearly in agreement with recent reports demonstrating that diet-induced obesity leads to modifications on the vitamin D metabolism, in the liver and in adipose tissue of mice, which may explain plasma vitamin D metabolites variations observed during obesity.…”
mentioning
confidence: 99%